Histopathological Changes by the Use of Soft Reline Materials: A Rat Model Study - Bail, Michele; Brol Meister, Lissandra Matos; Campagnoli, Eduardo Bauml; Jorge, Janaina Habib [UNESP]; Iglesias Ban, Manuella de Cassia; Sanchez-Ayala, Alfonso; Campanha, Nara Hellen (Public Library Science, 2014)
Aim: To assess the histopathological changes of rat palatal mucosa exposed to soft reline materials.Methods: Forty-five adult female Wistar rats with controlled living conditions and fed ad libitum were employed. Palatal appliances of heat-polymerized acrylic resin Lucitone 550 were manufactured and worn by forty animals during 14 days. Five animals did not use the appliances (G1) and were used to control the appliance influence. One experimental group (n = 10) used the appliances without any relining material (G2) to control the material effect. Three experimental groups (n = 10) received the following soft reline materials below appliances: Dentusoft (G3), Dentuflex (G4), and Trusoft (G5). Appliances from half of each experimental group(n = 5) was immersed in water bath at 55 degrees C for 10 min before use. Animals were slaughtered and the palates were fixed in 10% buffered formalin. Hematoxylin and eosin stained sections of 5 mu m were analyzed by computerized planimetry. Cellular compartment, keratin and total epithelial thickness, and basement membrane length were measured to histopathological description. Analysis of variance and Tukey post-hoc test were used to data examination(alpha = 0.05).Results: For heat-treatment groups, G4 showed less elongated ridges at the basal layer interface (p = 0.037) than G2. When comparing the conditions with and without heat-treatment, only G2 showed a significant decrease in the cellular compartment, keratin layer and total epithelium thickness (p<0.05).Conclusion: The post-polymerization for Lucitone 550 was an effective method to reduce the changes in the rat palatal mucosa. The soft reline materials tested did not cause significant histopathological changes in the rat palatal mucosa.